Intertidal beach profle estimation from reﬂected wave measurements - Almar, R. (2020)
The intertidal beach profle provides coastal engineers and managers with a good indication of the current state of a sandy coastline, however regular beach profle measurements are time consuming and expensive to obtain using conventional surveying methods. The potential to reconstruct the intertidal beach profle from measurements of reﬂected waves is tested here using three feld datasets covering a diﬀerent range of hydro-morphological conditions from dissipative, to reﬂective. The swash is found to behave as a low-pass flter on reﬂected waves, with a cut-oﬀ frequency that primarily depends on the swash slope. An agreement is found between video-derived swash spectrum saturation tail and the shortest reﬂected waves, computed from deep water directional wave measurements. By integrating this swash slope over a tidal cycle, the shape of the intertidal beach profle can be reconstructed. Our results clearly show the potential of such method to estimate complex intertidal beach profle, such as double-slope beaches.